Adolescent Perceptions of Premarital Sex Behavior in Cibinong Bogor - Nurmawati, Nurmawati; Tassya, Anas (JBKI (Jurnal Bimbingan Konseling Indonesia), 2024)
This study aims to determine the adolescent's perception of premarital sex behavior. This is motivated by teenagers, some of whom have negative perceptions of premarital sex behavior and some have positive perceptions of premarital sex behavior. This study uses a descriptive method with a quantitative approach. The population in this study amounted to 61,189 adolescents with a sample of 100 adolescents. The sampling technique is random sampling by taking samples through the Google From instrument with a Likert scale. Validity test using person product moment using SPSS and the results obtained are 25 items valid items. While the reliability test using Cronbach's Alpha using SPSS with the results of the reliability value of 0.724 > 0.6. So the data has a reliable instrument. The results of this study indicate that more adolescents have negative perceptions of premarital sex behavior compared to those who have positive perceptions. When viewed from the distribution of adolescent perceptions, it is known that from 100 adolescents who were respondents, it indicated that some respondents had negative perceptions as many as 55 respondents (55%) and almost half of respondents had positive perceptions, namely 45 respondents (45%).